Islamic Boarding Schools: Among Da'wah, Education, and Moderation Way in Islam - Vishkurti, Roland (Dakwah, 2022)
This article describes the education system and da'wah methods in Islamic boarding schools in the current era of information and communication technology advancement. In particular, in aspects related to nation building, both on a local and national scale in Indonesia. In fact, at the international level, where Indonesia can become a model mecca for Islamic education and da'wah for Islamic countries. in theory and concepts that are used as the basis for elaborating the topic in question are Wasathiyah Islam, national insight, entrepreneurship or entrepreneurship, and optimizing technology for the potential development of Islamic boarding schools. The method used for the preparation of this article is ethnography. A number of data collection and analysis techniques were carried out to formulate conclusions, including field observations, interviews, and literature review, both printed and presented in electronic media. Field observations and interviews were conducted on a digital basis. Either by observing through documentation on social media of Islamic boarding schools, or through interviews via email with a number of Islamic boarding school practitioners in Indonesia. The analysis was carried out through data reduction, presentation of discussions, and formulation of final results. Based on the research that has been done, it can be concluded that Indonesian Islamic boarding schools have the opportunity to become the axis of world Islamic moderation education. Moreover, so far, Islamic boarding schools in Indonesia have always campaigned for a central Islam, which is neither extreme nor liberal. Pesantren always instills national insight in the students and preaches it to the public. Islamic boarding schools teach independence in the economic field to students through a curriculum that has linearity with entrepreneurship. The use of Islamic boarding school social media as a support for the duties and functions of this educational institution is pursued in line with the progress of the times.